A method for predicting the drum strength of sintered ore in each material layer of a sintering trolley
By conducting ore phase analysis and micromechanical performance measurement of the samples to be tested on the sintered ore, a quantitative relationship model of the sintered ore was established, the problem of predicting the drum strength of each area of the sintered trolley was solved, and important guidance on sintered ore production was achieved.
Patent Information
- Application Number
- CN202111430078.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-29
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-11-29
AI Technical Summary
The prior art is difficult to accurately predict the drum strength of sintered ore in each area of the sintered trolley, and the inconvenience of sampling and testing affects the production of sintered ore.
By conducting ore phase analysis, micromechanical performance measurement and porosity statistics on the samples to be tested on the sintered ore, a quantitative relationship model between the porosity, typical mineral content, micromechanical performance and drum strength of the sintered ore is established, and the drum strength prediction of the drum strength of the sintered ore of each material layer of the sintered trolley is achieved.
The drum strength of sintered ore in different areas of the sintered trolley was achieved through simple sampling, and the important factors affecting the drum strength were clarified, providing important guidance for optimizing sintered ore production.
Smart Images

Figure GDA0004986274600000031 
Figure GDA0004986274600000041 
Figure GDA0004986274600000042
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sintered ore production, and in particular relates to a method for predicting the drum strength of sintered ore in each material layer of a sintering trolley. Background Art
[0002] With the continuous improvement of blast furnace smelting intensity, the quality requirements for sintered ore are also getting higher and higher. The drum strength is an important technical indicator to characterize the strength of sintered ore. Its level directly affects the yield of sintered ore and the technical and economic indicators of blast furnace smelting. Improving the drum strength of sintered ore is conducive to improving the particle size of sintered ore entering the furnace and thus improving the permeability of the upper part of the blast furnace, improving the utilization rate of coal gas, reducing the coke ratio of blast furnace smelting, and stabilizing the smooth operation of the blast furnace.
[0003] The drum strength of sintered ore is mainly tested according to the national standard. However, the national standard requires screening of the sintered ore, selecting sintered ore of different particle sizes for testing, and finally screening again to obtain the drum strength index of the sintered ore, which is time-consuming and labor-intensive.
[0004] At present, sintered ore is mainly produced through sintering trolleys, and the sintering trolleys are sintered by negative pressure exhaust, and ignition is carried out at the top of the material layer. The temperature of the top of the material layer changes very quickly. In addition, due to the heat storage effect of the material layer, the temperature is lower than that of the lower material layer; there is heat exchange between the side wall sample of the sintering trolley and the side wall of the trolley, and its temperature is relatively low, and there is an edge effect. Therefore, the return of sintered ore is currently mainly concentrated in the upper part and the side wall, but there is a lack of accurate understanding of the difference in drum strength of samples in different areas. However, it is extremely inconvenient to sample and test the sintering trolleys at present, and it also affects the normal production of sintered ore. Therefore, it is urgent to obtain a small amount of samples from different areas of the sintering trolley through simple sampling to predict the metallurgical properties of each area of the sintering trolley. This method can accurately predict the drum strength of different areas of the sintering trolley, which has important guiding significance for improving the production of sintered ore. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for predicting the drum strength of sintered ore in each area of a sintering car in response to the deficiencies in the above-mentioned prior art, so as to achieve accurate understanding of the differences in drum strength of samples of different material layers and overcome the current technical difficulties that sampling and testing of sintering cars is extremely inconvenient and also affects the normal production of sintered ore.
[0006] The technical solution adopted by the present invention to solve the above-mentioned problems is:
[0007] A method for predicting the drum strength of sintered ore in each material layer of a sintering trolley comprises the following steps:
[0008] S1, respectively performing mineral phase analysis on the sintered ore samples to be tested in each material layer of the sintered ore trolley to determine the typical minerals constituting the sintered ore samples to be tested, and then measuring the microscopic mechanical properties of the typical minerals; and quantitatively calculating the typical mineral content and porosity of the sintered ore samples to be tested;
[0009] S2, based on the trolley production raw materials, sintering cup experiments were carried out under different process conditions to obtain different sintered ores, and then drum strength tests were carried out. At the same time, the porosity, typical mineral content, and microscopic mechanical properties of typical minerals of the sintered ores were tested and analyzed, and a quantitative relationship model between the porosity, typical mineral content, and microscopic mechanical properties of typical minerals of the sintered ores and the drum strength of the sintered ores was established;
[0010] S3, substituting the porosity, typical mineral content and corresponding mineral microscopic mechanical properties of the sintered ore samples to be tested in each material layer obtained in step S1 into the first quantitative relationship model obtained in step S2, so as to obtain the drum strength of the sintered ore samples to be tested, and realize the prediction of the drum strength of the sintered ore samples to be tested in each material layer of the sintering trolley.
[0011] According to the above scheme, in step S1, the sintered ore sample to be tested is subjected to mineral phase analysis by using XRD and SEM analysis to determine the typical mineral composition of the sintered ore samples in each material layer.
[0012] According to the above scheme, typical minerals of sintered ore are mainly: hematite, magnetite, calcium ferrite and silicate.
[0013] According to the above scheme, in step S1 and step S2, the Vickers hardness of each typical mineral is tested using a microhardness tester as a micromechanical property.
[0014] According to the above scheme, in step S2, the specific process of quantitatively counting the typical mineral content and porosity is as follows: quantitatively counting the typical mineral content and porosity of the sintered ore samples to be tested in each material layer by optical microscopy based on the panoramic mineral phase area statistical method, wherein the sum of each typical mineral content and porosity is 100%; each material layer has at least three sintered ore samples to be tested, with a total area of at least 600mm 2 .
[0015] According to the above scheme, in step S2, the specific process of conducting the sintering cup experiment under different process conditions based on the raw materials produced by the trolley is: using the raw fuel used in the actual trolley production to conduct the sintering cup experiment to ensure the consistency of the thickness of the sintering material layer, and changing the process including: the moisture content of the mixture, the ratio of iron ore powder, the ratio of fuel, and ensuring the consistency of alkalinity.
[0016] According to the above scheme, in step S2, the test method for the typical mineral microscopic mechanical properties of the sintered ore and the quantitative statistical method for the typical mineral content and porosity are consistent with those in step S1.
[0017] According to the above scheme, in step S2, the specific process of establishing the first quantitative relationship model between the porosity, typical mineral content, typical mineral microscopic mechanical properties and drum strength of the sintered ore is: weighting the typical mineral content and its corresponding microscopic mechanical properties as the strength index of the typical mineral, and establishing the first quantitative relationship model between the porosity of the sintered ore, the typical mineral phase strength index and the drum strength based on the partial least squares method. Among them, the specific process of weighting the typical mineral content and its corresponding microscopic mechanical properties as the strength index of the typical mineral is: multiplying the microscopic mechanical properties of each typical mineral with its corresponding percentage content as the strength index of the typical mineral.
[0018] According to the above scheme, in step S3, the content of each typical mineral and the corresponding mineral phase microscopic mechanical properties are converted into the mineral phase strength index required by the first quantitative relationship model, and then substituted into the first quantitative relationship model together with the porosity to obtain the drum strength of the sintered ore sample to be tested.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1) The method for predicting the drum strength of each area of the sintering trolley provided by the present invention predicts the metallurgical properties of each area of the sintering trolley by simply sampling a small amount of samples from different material layers of the sintering trolley, thereby realizing the rapid acquisition of the drum strength of sintered ore in different areas of the sintering trolley through micro-sampling and micro-testing.
[0021] 2) The method for predicting the drum strength of each area of the sintering trolley provided by the present invention can obtain the drum strength of sintered ore in different areas of the sintering trolley, clarify the most important factors affecting the drum strength of sintered ore, and play an important guiding role in optimizing sintered ore production and improving sintered ore quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a process flow chart of the method for predicting the drum strength of sintered ore in each area of the sintering car described in the present invention.
[0023] Figure 2 Panoramic view of sintered ore of sample 1;
[0024] Figure 3 Panoramic view of sintered ore of sample 2;
[0025] Figure 4 Panoramic view of sintered ore of sample 3;
[0026] Figure 5 Panoramic view of sintered ore of sample 4;
[0027] Figure 6 Panoramic view of sintered ore of sample 5;
[0028] Figure 7Panoramic view of the sintered ore sample of Example 2. DETAILED DESCRIPTION
[0029] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the present invention is not limited to the following embodiments.
[0030] In the following examples, there are no less than three sintered ore samples to be tested in each material layer, with a total area of no less than 600mm 2 .
[0031] Example 1
[0032] A method for predicting the drum strength of sintered ore in each material layer of a sintering trolley comprises the following steps:
[0033] S1, stratified sampling and analysis of the sintered ore of each material layer of the sintering ore trolley, a total of 5 layers from top to bottom, samples 1-5 are taken in sequence (where samples 1-5 correspond to material layers 1-5, respectively, sample 1 corresponds to the top layer of the material layer, and sample 5 corresponds to the bottom layer of the material layer), and XRD and SEM analysis are performed on samples 1-5 respectively to obtain typical minerals in samples 1-5, including hematite, magnetite, calcium ferrite and silicate;
[0034] Then, the porosity and typical mineral content of samples 1-5 were statistically analyzed based on the panoramic mineral phase diagram statistical method, wherein a panoramic mineral phase diagram of each layer of the sample is as follows: Figure 2-Figure 6 The statistical results of typical mineral contents are shown in Table 1.
[0035] Table 1 Typical mineral content of different layers (%)
[0036]
[0037] The micromechanical properties of typical minerals in samples 1-5 were tested using Vickers hardness test, and the results are shown in Table 2.
[0038] Table 2 Micromechanical properties of typical minerals in different layers (HV)
[0039]
[0040] S2, based on the raw materials produced by the trolley, 9 groups of sintering cup experiments (serial number 1-9) were carried out under different process conditions, and the material layer thickness of the sintered ore obtained by the sintering cup experiment was ensured to be consistent with that of the sintering trolley, which was 700 mm. Then, the drum strength of the sintered ore obtained by the sintering cup experiment was tested. At the same time, the typical mineral content of the sintered ore obtained by the sintering cup experiment was statistically analyzed based on the panoramic mineral phase threshold segmentation method. Then, the microscopic mechanical properties of the typical minerals of the sintered ore obtained by the sintering cup experiment were tested using a Vickers hardness tester.
[0041] Based on the current raw materials and fuels of the sintering trolley, the sintering cup test was carried out by changing the iron ore powder ratio, fuel ratio and moisture content in the sintering mixture, while ensuring that the central value of the alkalinity of the sintered ore was 1.85; wherein, the sintering mixture was sintered with an appropriate amount of water, the iron ore powder ratio and fuel ratio respectively refer to the mass percentage of iron ore powder and fuel in the sintering mixture, and the moisture content refers to the mass percentage of moisture in the total amount of moisture and the sintering mixture; at the same time, the different process conditions of the sintering cup experiment and the drum strength results of the sintered ore obtained under the corresponding process conditions are shown in Table 3.
[0042] Table 3 Process conditions of sintering cup test and drum strength of sintered ore
[0043]
[0044] Then, the typical mineral content and porosity of the sintered ore obtained from the sintering cup test are shown in Table 4, and the micromechanical properties of the typical minerals are tested, and the results are shown in Table 5.
[0045] Table 4 Porosity and mineral phase content of sintered ore obtained from sintering cup test (%)
[0046]
[0047]
[0048] Table 5 Typical mineral micromechanical properties of sintered ore obtained from sintering cup test (HV)
[0049]
[0050] A quantitative relationship model between the porosity, typical mineral content, typical mineral microscopic mechanical properties and drum strength of the sintered ore obtained from the sintering cup experiment was established. Specifically, the microscopic mechanical properties of each typical mineral were multiplied by its corresponding content as the typical mineral strength index. Then, based on the partial least squares method, a quantitative model between the porosity, each typical mineral strength index and drum strength was established as follows:
[0051] T=62.4842-0.102×pore%-0.008*H-0.006*M+0.014*SFCA+0.0275*G········R 2 =0.93
[0052] Wherein: T is the drum strength of the sintered ore, in %; pore% is the porosity of the sintered ore, in %; H is the strength index of hematite, in HV%; M is the strength index of magnetite, in HV%; SFCA is the strength index of calcium ferrite, in HV%; G is the strength index of silicate, in HV%.
[0053] S3. The strength index of each typical mineral is obtained by weighted calculation according to the typical mineral content of samples 1-5 and its corresponding micromechanical properties. The strength index and porosity in Table 1-2 are substituted into the quantitative relationship model obtained in step S2 to obtain the drum strength of samples 1-5 as shown in Table 7.
[0054] Table 7 Prediction results of sinter drum strength for different material layers
[0055]
[0056] It can be seen from Table 7 that the upper drum strength of the sintered ore is poor, mainly because of the high porosity and low strength of calcium ferrite. Based on this result, the process is adjusted to improve the problem of low strength of the upper drum of the sintered ore, so as to improve the strength improvement effect of the sintered ore.
[0057] In addition, according to the drum strength index model, it can be seen that reducing the porosity, hematite strength and magnetite strength index is conducive to improving the drum strength of sintered ore, and increasing the calcium ferrite and silicate strength index is conducive to increasing the drum strength of sintered ore. In order to quantitatively analyze the influencing index of each factor on the drum strength and reveal the most important factors affecting the drum strength of sintered ore, the influence of each factor on the drum strength is quantitatively analyzed, and the analysis results are shown in Table 8.
[0058] It can be seen from Table 8 that the influence on drum strength is in the following order: porosity > calcium ferrite strength > hematite strength > silicate strength > magnetite strength. Therefore, the porosity and calcium ferrite strength have the greatest influence. Reducing the porosity of sintered ore and improving the calcium ferrite strength index have the greatest improvement on drum strength. Improving the calcium ferrite strength index can increase the calcium ferrite content and improve the micromechanical properties of calcium ferrite.
[0059] Table 8 Analysis of the influence of various factors on the sinter drum strength
[0060]
[0061] Example 2
[0062] In order to verify the accuracy of the method for predicting the drum strength of sintered ore in each material layer of the sintering trolley described in the present invention, a sintering cup experiment was carried out based on the raw materials produced by the trolley, as in Example 1. The experimental conditions were: moisture content 6.5%, fuel ratio 4.2%, iron ore powder ratio 40%, and the drum strength of the sintered ore was 63.60.
[0063] Then, random sampling was performed for mineral content statistics and micromechanical property analysis. The mineral content, porosity and mineral microscopic hardness are shown in Tables 9-10. The predicted value of drum strength calculated by the quantitative model in Example 1 is:
[0064] T=62.4842-0.102*27.45-0.008*113.88-0.006*127.35+0.014*261.94+0.0275*72.8=63.68. The error between the predicted value and the actual experimental result 63.60 is only 0.13%.
[0065] Table 9 Mineral phase area content and porosity / %
[0066] Mineral Type Porosity Silicate Calcium Ferrite magnetite Hematite Mineral Content 27.45 11.06 31.72 17.57 12.19
[0067] Table 10 Mineral micromechanical properties / HV
[0068] Mineral Type Silicate Calcium Ferrite magnetite Hematite Microhardness 658.3 825.8 724.8 934.2
[0069] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for predicting the drum strength of sintered ore in each material layer of a sintering trolley, characterized in that: The steps include: S1, respectively performing mineral phase analysis on the sintered ore samples to be tested in each material layer of the sintered ore trolley to determine the typical minerals constituting the sintered ore samples to be tested, and then measuring the microscopic mechanical properties of the typical minerals; and quantitatively calculating the typical mineral content and porosity of the sintered ore samples to be tested; S2, based on the trolley production raw materials, sintering cup experiments were carried out under different process conditions to obtain different sintered ores, and then drum strength tests were carried out. At the same time, the porosity, typical mineral content, and microscopic mechanical properties of typical minerals of the sintered ores were statistically analyzed and tested, and a quantitative relationship model between the porosity, typical mineral content, and microscopic mechanical properties of typical minerals of the sintered ores and the drum strength of the sintered ores was established; S3, substituting the porosity, typical mineral content and corresponding mineral micromechanical properties of the sintered ore samples to be tested of each material layer obtained in step S1 into the first quantitative relationship model obtained in step S2, thereby obtaining the drum strength of the sintered ore samples to be tested, and realizing the prediction of the drum strength of the sintered ore samples to be tested of each material layer of the sintering trolley; In step S1, the specific process of quantitatively counting the typical mineral content and porosity is as follows: quantitatively counting the typical mineral content and porosity of the sintered ore sample to be tested in each material layer by optical microscopy based on the panoramic mineral phase area statistical method, wherein the sum of each typical mineral content and porosity is 100%; In step S2, the specific process of establishing the first quantitative relationship model between the porosity, typical mineral content, typical mineral microscopic mechanical properties and drum strength of the sintered ore is as follows: weighting the typical mineral content and its corresponding microscopic mechanical properties as the strength index of the typical mineral, and establishing the first quantitative relationship model between the porosity of the sintered ore, the typical mineral phase strength index and the drum strength based on the partial least squares method; The specific process of weighting the typical mineral content and its corresponding microscopic mechanical properties as the strength index of the typical mineral is: multiplying the microscopic mechanical properties of each typical mineral with its corresponding percentage content as the strength index of the typical mineral.
2. The method for predicting the drum strength of sintered ore in each area of a sintering trolley according to claim 1, characterized in that: In step S1, the sintered ore sample to be tested is subjected to mineral phase analysis by using XRD and SEM analysis to determine the typical mineral composition of the sintered ore samples in each material layer.
3. The method for predicting the drum strength of sintered ore in each area of a sintering trolley according to claim 1, characterized in that: Typical minerals of sintered ore are: hematite, magnetite, calcium ferrite and silicate.
4. The method for predicting the drum strength of sintered ore in each area of a sintering trolley according to claim 1, characterized in that: The Vickers hardness of typical minerals was tested using a microhardness tester as a micromechanical property.
5. The method for predicting the drum strength of sintered ore in each area of a sintering trolley according to claim 1, characterized in that: The specific process of conducting the sintering cup experiment under different process conditions based on the raw materials produced by the trolley in step S2 is: using the raw fuel used in the actual trolley production to conduct the sintering cup experiment to ensure the consistency of the thickness of the sintering material layer, and changing the process including: the moisture content of the mixture, the ratio of iron ore powder, the fuel ratio, and ensuring the consistency of alkalinity.
6. The method for predicting the drum strength of sintered ore in each area of a sintering trolley according to claim 1, characterized in that: The test method for the typical mineral microscopic mechanical properties of the sintered ore in step S2 and the quantitative statistical method for the typical mineral content and porosity are consistent with those in step S1.